Evaluation of the predominant musculoskeletal diseases in participants of a chronic pain group in a UBS in Ceilândia (Research, Society and Development, 2022)
Chronic is defined as a sensory and emotional experience, being subjective in each individual, based on their traumatic experiences, being persistent, continuous or recurrent events, lasting at least three months and of a biopsychosocial nature. The study aimed to control the duration, intensity and locations of the most frequent musculoskeletal pain in participants of a chronic pain group at a UBS in Ceilândia - Distrito Federal. Eight people were interviewed, between 4 people and 8 years old, and one person was applied to obtain personal information, life habits, previous treatments and healthy aspects. To measure pain intensity, use the Visual Analog Scale (VAS), it is a 10 cm straight line, where zero indicates no pain and 10 the worst possible. An analysis of the results showed that the average response score of the participants' general quality of life, of 6.37 points in the first period and 6.25 in the second period and data collection, and the best quality of life observed in the physical and psychological factors in the second period when compared to the first period and in the environmental domain. Regarding the predominant pain in the group that was studied in relation to musculoskeletal pain, the spine was related to the segment that is most affected by pain.